Respuesta :
-3/5 = (f-g))/(11-f))
we use cross products to help solve the problem
top on the left times bottom of the right = top on the right times bottom on the left
5(f-g)= -3(11 - f)
distribute
multiply the number on the outside of the parenthesis to the terms on the inside
5*f -5*g = -3*11 -3* (-f)
5f-5g = -33 +3f
subtract 3f from each side
2f -5g = -33
The nine clarifies the problem.
5(f - 9) = -3(11 - f) Remove the brackets. Here we have the distributive property in action. We are showing how to remove the common fact outside the brackets so we can solve for the equation.
5f - 5*9 = -3 * 11 - 3*f Combine
5f - 45 = -33 + 3f Add 45 to both sides.
5f - 45 + 45 = - 33+ 45 + 3f Combine
5f = 12 + 3f Subtract 3f from both sides
5f - 3f = 12 + 3f - 3f Combine
2f = 12 Divide by 2
2f/2 = 12/2
f = 6 Answer